The Impact of Childhood Malnutrition: A Case Report - Chandni P. Daryanani; Bryan Kohen; Ellen G White Br Manik; Joseph Gerard Un Nahak; Xena Syafira (Rumah Sakit Unggul Karsa Medika, 2023)
Childhood malnutrition is a widespread issue in low-income and middle-income countries, which increases the occurrence and severity of infections, including pneumonia. The impaired immune function of malnourished children contributes significantly to the heightened incidence and severity of infections, caused by limited production or reduced functional capacity of immune system cells